The Role of Spirituality in Treatment Outcomes Following a Residential 12-Step Program. Issue 1 (2nd January 2017) - Ranes, Bethany; Johnson, Ryan; Nelson, Lindsay; Slaymaker, Valerie
ABSTRACT: Alcoholics Anonymous (AA) and other 12-Step treatment programs emphasize the positive effects of spirituality on abstinence from alcohol; however, the associations among positive treatment outcomes, spirituality, and other psychological constructs have received limited empirical attention. The present study attempts to better define the nature of spirituality, while also examining its role alongside relevant psychological constructs in treatment outcomes for patients who attend a residential 12-Step program. Data collected at treatment entry, treatment discharge, and 1-, 6-, and 12-months postdischarge supported the conclusion that spirituality is a dynamic construct that is distinct from, but related to, traditional religiousness, and is significantly associated with a participant's affect and meaning in life. Participants demonstrated a significant increase in spirituality upon completion of a residential 12-Step treatment program. Although there was no support for a direct association between spirituality and abstinence following treatment, AA participation appeared to play a mediating role between the two variables, which suggests that increased spirituality can have an indirect positive effect on abstinence through its association with increased AA participation.